Juvenile idiopathic arthritis in Harlequin ichthyosis, a rare combination or the clinical spectrum of the disease? Report of a child treated with etanercept and review of the literature - Francesco Baldo; Michela Brena; Simone Carbogno; Francesca Minoia; Stefani Lanni; Sophie Guez; Antonella Petaccia; Carlo Agostoni; Rolando Cimaz; Giovanni Filocamo (BMC, 2021)
Abstract Background Harlequin ichthyosis (HI) is the most severe phenotype of autosomal recessive congenital ichthyosis. Juvenile Idiopathic Arthritis (JIA) represents a heterogenous group of disorders all sharing the clinical manifestation of chronic arthritis. Association of HI and chronic arthritis has been reported in few cases. Case presentation We report the case of a child with HI who developed a severe form of chronic polyarthritis during the first years of life, treated with repeated multiple joint injections, methotrexate and etanercept with good response and without any adverse events. Conclusion The reported case and the literature review highlighted the presence of a peculiar severe seronegative polyarthritis with early onset in a series of patients with HI, suggesting that polyarthritis may be a specific manifestation of HI, rather than a rare combination of two separate conditions.